2020
DOI: 10.1080/14767333.2020.1712842
|View full text |Cite
|
Sign up to set email alerts
|

Action learning and action research to alleviate poverty

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For example, although regular financial assistance can eliminate poverty at times, educational programs help alleviate poverty over time especially in the intergenerational transmission of poverty (Guo et al, 2019). Studies have shown that educational activities can significantly contribute positive changes for individuals, societies, economies and viewed as a fundamental solution for all issues (Boak et al, 2020;Brown & James, 2020) The fourth SDG set by the United Nations (UN) is on education aiming to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. In addition, the education goal is targeted to ensure, among others, that all learners acquire knowledge and skills needed to promote sustainable development including promotion of sustainable lifestyles, a culture of peace and non-violence,…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%
“…For example, although regular financial assistance can eliminate poverty at times, educational programs help alleviate poverty over time especially in the intergenerational transmission of poverty (Guo et al, 2019). Studies have shown that educational activities can significantly contribute positive changes for individuals, societies, economies and viewed as a fundamental solution for all issues (Boak et al, 2020;Brown & James, 2020) The fourth SDG set by the United Nations (UN) is on education aiming to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. In addition, the education goal is targeted to ensure, among others, that all learners acquire knowledge and skills needed to promote sustainable development including promotion of sustainable lifestyles, a culture of peace and non-violence,…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%